2014
DOI: 10.5005/jp-journals-10024-1507
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Burs on the Topography of Smear Layer Formation on the Dentinal Surface: A Scanning Electron Microscope Study

Abstract: Whenever a hand or a rotary instrument is used to eliminate tooth tissue, the mineralized matrix shatters rather then being uniformly sheared, producing considerably quantities of cutting debris. Much of the debris made up of very small particles of mineralized collagen matrix over the surface of dentin is known as smear layer. The clinical outcome of dental restorations is dependent upon the surface preparations, smear layer formation and hybrid layer which which provides a stable adhesion. Different surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
0
2
3
Order By: Relevance
“…The thickness of the smear layer is also affected by type of the bur used. Several studies have demonstrated that carbide bur produces thinner smear layer compared to that of diamond bur [27][28][29]. However, the current study showed the mean ± S.D.…”
Section: Discussioncontrasting
confidence: 79%
“…The thickness of the smear layer is also affected by type of the bur used. Several studies have demonstrated that carbide bur produces thinner smear layer compared to that of diamond bur [27][28][29]. However, the current study showed the mean ± S.D.…”
Section: Discussioncontrasting
confidence: 79%
“…Several studies have demonstrated that carbide bur produces thinner smear layer compared to that of diamond bur. 24,25,26 However, the current study showed the mean±S.D OD of GIC-Carbide and GIC-Diamond, MTA-Carbide and MTA-Diamond and Biodentine-Carbide and Biodentine-Diamond respectively with statistically non-significant difference (p = 1.000). Hence, in this study, the comparable nature of two different retrograde preparations were observed and can be used according to ease.…”
Section: Discussioncontrasting
confidence: 64%
“…Several studies have demonstrated that carbide bur produces thinner smear layer compared to that of diamond bur. 27,28,29 However, the current study showed the mean±S.D OD of GIC-Carbide and GIC-Diamond, MTA-Carbide and MTA-Diamond and Biodentine-Carbide and Biodentine-Diamond respectively with statistically non-significant difference (p=1.000). Hence, in this study, the comparable nature of two different retrograde preparations were observed and can be used according to ease.…”
Section: Concluded Thatcontrasting
confidence: 64%